SEQUENCE BIOSTRATIGRAPHY AND PALEOENVIRONMENTAL RECONSTRUCTION IN THE EARLY EOCENE FIGOLS GROUP OF THE TREMP-GRAUS BASIN (SOUTH-CENTRAL PYRENEES, SPAIN) - Torricelli S.; Knezaurek G.; Biffi U. (My University, 2006)
The dinoflagellate cyst, palynofacies and foraminiferal records from the Early Eocene Figols Group of the Spanish Pyrenees exhibit major changes associated with relative sea-level fluctuations and variations in efficiency of the fluvial systems. The mixed siliciclastic-carbonate marine succession exposed in the Merli-Esdolomada area was deposited on the shelf in a tectonically active basin, under oxic conditions, in shallow to moderately deep marine waters (close to the lower boundary of the photic zone) influenced by river discharge from adjacent emerged lands. Sedimentary cycles are mainly recorded by fine-grained deposits. The paleoenvironmental interpretation of palynological and calcareous microfaunal records allows the definition of depositional sequences and enables to trace basinward surfaces identified in more proximal settings by means of sedimentological facies analysis. At the same time, the solid regional stratigraphic framework already available for the Figols Group allows new insights on the paleoecology of extinct taxa. The Merli-Esdolomada section (ME) spans two 3rd order sequences. The upper sequence reflects more marginal marine conditions than the lower one, thus pointing to an overall shallowing trend with time. In the lower sequence the maximum flooding interval is characterised by a rich and diverse microfauna, highest relative abundances of marine phytoplankton and typically neritic dinoflagellate cyst (dinocyst) assemblages dominated by Spiniferites and Cordosphaeridium. The final phase of the highstand systems tract, in proximity of the main sequence boundary, is characterised by a decrease in abundance and diversity of dinocysts, with the dominance of the lagoonal genus Polysphaeridium, and by decreased microfaunal diversity (discorbids, miliolids, larger foraminifers). Palynological records permit the reconstruction of activation and deactivation phases of the fluvial systems, variations in runoff from the hinterland, nutrient delivery to the sea and productivity in surface waters of the Tremp-Graus Basin. The overall abundance of Spiniferites and the scarcity of peridinioid cysts, Lingulodinium, Pediastrum and Botryococcus algae are interpreted to indicate oligotrophic conditions during the deposition of the investigated succession. Recurrent intervals where the temporary disappearance of Spiniferites corresponds to highest relative abundances of Operculodinium and herbaceous debris are the main evidence for river plumes and denote periods of enhanced fluvial discharge reflecting a Milankovitch-type cyclicity. The Rotalia group, which shows abundance peaks of Cuvillierina spp. in the shallower intervals, is often associated with these episodes, thus suggesting for this taxon more tolerance to turbidity than larger foraminifera. Within the maximum flooding zone, a Thalassiphora patula acme corresponding to the local disappearance of Homotryblium is deemed to record the distal expression of a fluvial activation which triggered water salinity stratification. Despite broad morphological similarities, Homotryblium exhibits more cosmopolitan preferences than Polysphaeridium, which is instead confirmed as a lagoonal euryhaline taxon. The increase of Spinizonocolpites pollen toward the top of the Figols Group records the northwestward migration of Nypa mangrove-palms from southern Europe during the mid Early Eocene. © 2005 Elsevier B.V. All rights reserved.
Keywords: DINOFLAGELLATE CYSTS; EARLY EOCENE; FORAMINIFERS; PALEOECOLOGY; SEQUENCE STRATIGRAPHY; SPANISH PYRENEES; Eocene; Cenozoic::Paleogene::Eocene; Кайнозой::Палеоген::Эоцен